A Case Report of High 18F-FDG PET/CT Uptake in Progressive Transformation of the Germinal Centers. Issue 23 (June 2015) - Chang, Chian A.; Kumar, Beena; Nandurkar, Deepali; Sinha., Partha
<x xml:space="preserve">Abstract</x> Abstract Progressive transformation of the germinal centers (PTGC) is a benign reaction pattern in lymph nodes. An association with Hodgkin disease (HD) has been reported and PTGC may precede, coexist, or present after the diagnosis of HD. This case report describes a patient who presented with unprovoked pulmonary embolism and subsequent investigations showed a solitary abdominal mass, which was subsequently proven to be PTGC. PTGC is usually avid on fluorine-18-labeled fluorodeoxyglucose positron emission tomography with computed tomography for attenuation correction and may be mistaken for neoplastic disease. Being a reactive etiology, the metabolic activity is generally low with a low maximum standardized uptake value (SUVmax), but in our case, the metabolic activity and corresponding SUVmax were relatively high making the diagnosis difficult, as most clinicians would consider a high metabolically active process more likely malignant. Recognition of PTGC is important, as it is not a malignant process. Owing to its reported associations, however, patients with this diagnosis will likely require regular surveillance.